Students’ Perceptions of the Use of Blogs in English Language Learning - Miftachudin Miftachudin (IAIN Salatiga, 2017)
This study aims to provide understanding about students’ perceptions of the benefits of blogs in English language learning and their challenges in authoring blogs. Unlike standard websites, blogs provide free and simple platforms that can be used by students without knowledge of computer language. Blogs can be considered as a new authentic English language learning environment in which reflection and collaboration take place. In addition, this study explores the benefits of blogs in English language learning. Furthermore, it investigates the challenges in authoring blogs that potentially define the gaps between students’ perceptions and blogging practice in English language learning. This study involves three undergraduate students at the State Institute for Islamic Studies (IAIN) Salatiga. It is conducted by using two stages of semi-structured interviews through Skype. The findings from the data analysis outline that the students perceive blogs as a beneficial application for English language learning in the areas of writing, reading and communication. However, they also admit that challenges remain in authoring blogs, such as performance fluctuation, self-confidence and aspects of technology. From the findings, there is a suggestion to formulate strategies in order to counteract the challenges. Thus, the use of blogs improves the quality of English language learning in any future practice.